Strategi Dakwah Bubohu sebagai Objek Wisata Dakwah di Bumi Gorontalo pada Masa Pandemi - Dian Adi Perdana; Rois Lantuka; Zulfahmi Kusuma; Julaeha Mingolo; Indah C Wewengkang; Hamdani; Akbar Lakisa (UIN Raden Mas Said Surakarta, 2022)
The Bubohu Kingdom is a symbol of Islam and Gorontalo culture, empowering the community, cultivating a micro-economy and a centre for the spread of Islam. This study examines the Islamic da'wah of the Bubohu Kingdom which developed into a da'wah tourism location in Gorontalo. This research is qualitative with a field research method. This study identifies the strategy and process of spreading da'wah that occurs in Bubohu Tourism so that it has an allure as a tourist attraction with a variable base of Islam, da'wah and history in Gorontalo. The results of this study were the strategy of preaching the Kingdom of Bubohu by conveying Islamic teachings to the people of Bubohu Gorontalo, cultivating customary principles based on syara, syara with scriptures. The missionary tourism of the Bubohu Kingdom began with the construction of a site and has since developed with several facilities, namely a natural boarding school, a museum of Indonesian wood fossils, a Bubohu Tourism Vocational School, and an organic agriculture laboratory.